Classification: theory and practice, de Ann F. Painter - Campos, Astério (Revista de Biblioteconomia de Brasília, 1975)
PAINTER, Ann F. Classification: theory and practice. Drexel Library Quarterly, v.10, n.4, p.1-120, Oct. 1974. (Este fascículo contém 8 artigos.)